1997
DOI: 10.1007/s004420050251
|View full text |Cite
|
Sign up to set email alerts
|

Leaf damage by herbivores affects attractiveness to pollinators in wild radish, Raphanus raphanistrum

Abstract: We carried out two experiments to determine the effect of leaf damage on plant attractiveness to pollinators using wild radish, Raphanus raphanistrum (Brassicaceae), a self-incompatible annual herb. Pairs of plants from 36 full-sib families were grown in pots in the greenhouse. One member of each pair was damaged by Pieris rapae larvae that were allowed to remove half of the leaf area of each of the first four rosette leaves. The plants were subsequently taken out for pollinator observations once a week from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
3
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 49 publications
3
128
3
6
Order By: Relevance
“…Similar results were noted in desert populations of A. aestivus, where the mirid bug's feeding included flower buds and flowers (Ayal and Izhaki 1993): damage to the buds would most likely cause a reduction in the total number of flowers. Production of fewer flowers because of herbivory is not rare and has been observed on other plants also (Karban and Strauss 1993;Quesada et al 1995;Strauss et al 1996;Juenger and Berelson 1997;Lehtilä and Strauss 1997;Mothershead and Marquis 2000). This activity may exert an important influence on reproductive success, as it can reduce the plant's attractiveness to pollinators and thereby reduce its fitness (Willson and Price 1976;Strauss et al 1996;Lehtilä and Strauss 1997;Keasar et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were noted in desert populations of A. aestivus, where the mirid bug's feeding included flower buds and flowers (Ayal and Izhaki 1993): damage to the buds would most likely cause a reduction in the total number of flowers. Production of fewer flowers because of herbivory is not rare and has been observed on other plants also (Karban and Strauss 1993;Quesada et al 1995;Strauss et al 1996;Juenger and Berelson 1997;Lehtilä and Strauss 1997;Mothershead and Marquis 2000). This activity may exert an important influence on reproductive success, as it can reduce the plant's attractiveness to pollinators and thereby reduce its fitness (Willson and Price 1976;Strauss et al 1996;Lehtilä and Strauss 1997;Keasar et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Production of fewer flowers because of herbivory is not rare and has been observed on other plants also (Karban and Strauss 1993;Quesada et al 1995;Strauss et al 1996;Juenger and Berelson 1997;Lehtilä and Strauss 1997;Mothershead and Marquis 2000). This activity may exert an important influence on reproductive success, as it can reduce the plant's attractiveness to pollinators and thereby reduce its fitness (Willson and Price 1976;Strauss et al 1996;Lehtilä and Strauss 1997;Keasar et al 2008). Environmental conditions such as temperature and humidity have been regarded in the past as major factors in determining nectar yield (Corbet 1978;Bertsch 1983;Pleasants 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The principal pollinators, i.e the native bees and syrphid flies, showed a preference for undamaged plants, visiting them more frequently and spending more time on them compared with those damaged by Pieris rapae larvae (Strauss et al 1996). However, bees, unlike the flies, did not distinguish between damaged and undamaged plants when flower numbers were controlled (Lehtilä and Strauss 1997). Under herbivory, male fitness traits, such as pollen size and number, were reduced, whereas female fitness traits, such as ovule size and number, were not affected (Lehtilä and Strauss 1999).…”
Section: Response To Parasitesmentioning
confidence: 99%
“…Numerous studies have shown that leaf damage can alter floral attractive traits that influence pollinator attraction (Adler 2007) such as flower number Strauss 1997, Hamback 2001), flower size (Aizen and Raffaele 1996, Strauss et al 1996, Lehtila¨and Strauss 1997, Mothershead and Marquis 2000, nectar production or quality (Adler et al 2006, Samocha andSternberg 2010), and floral volatiles Halitschke 2009, Theis et al 2009). These changes can reduce pollinator attraction (Strauss et al 1996, Lehtila¨and Strauss 1997, Mothershead and Marquis 2000 Halitschke 2009), with negative consequences for plant reproduction (Strauss and Murch 2004). For example, leaf herbivory in Oenothera macrocarpa (Onagraceae) resulted in smaller flowers that attracted fewer pollinators, reducing both fruit set and seed production as a result of pollen limitation (Mothershead and Marquis 2000).…”
Section: Introductionmentioning
confidence: 99%